PENGARUH PENGGUNAAN PUPUK KANDANG DAN NPK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH - Fauzia Hulopi (Universitas Tribhuwana Tunggadewi, 2006)
A field experiment that was conducted at Ketanggi Village, Karangploso District of Malang Regency in May-September 2007, was aimed to study the effects of farmyard manure and NPK fertilizers on growth and yield of groundnut. Data were collected through measurements of plant height, number of branch, number of leaves, plant biomass weight, wet and dry weight of ‘polong’ number of ‘polong’, and weight of 100 dry seeds. Results of the study showed that there was no significant interaction between farmyard manure and NPK fertilizer treatments at all measured variables. Results of separate statistical analyses, however, showed that application of farmyard manure and NPK fertilizer with a rate of 20g/plot could improve growth ands yield of groundnut